Law No. 78 of the year 2017 On Granting An Exceptional Cost-of-living Allowance to the State Civil Servants Who Are Not Addressed with the Civil Service Law = قانون رقم 78 لسنة 2017 بمنح علاوة استثنائية للعاملين بالدولة من غير المخاطبين بقانون الخدمة المدنية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic